A novel dendritic nanocarrier of polyamidoamine-polyethylene glycol-cyclic RGD for “smart” small interfering RNA delivery and in vitro antitumor effects by human ether-à-go-go-related gene silencing in anaplastic thyroid carcinoma cells - Li G (Dove Medical Press, 2013)
Guanhua Li,1,2 Zuojun Hu,1 Henghui Yin,1 Yunjian Zhang,1 Xueling Huang,1 Shenming Wang,1 Wen Li2 1Department of Vascular and Thyroid Surgery, 2Key Laboratory of Surgery, The First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People's Republic of China Abstract: The application of RNA interference techniques is promising in gene therapeutic approaches, especially for cancers. To improve safety and efficiency of small interfering RNA (siRNA) delivery, a triblock dendritic nanocarrier, polyamidoamine-polyethylene glycol-cyclic RGD (PAMAM-PEG-cRGD), was developed and studied as an siRNA vector targeting the human ether-à-go-go-related gene (hERG) in human anaplastic thyroid carcinoma cells. Structure characterization, particle size, zeta potential, and gel retardation assay confirmed that complete triblock components were successfully synthesized with effective binding capacity of siRNA in this triblock nanocarrier. Cytotoxicity data indicated that conjugation of PEG significantly alleviated cytotoxicity when compared with unmodified PAMAM. PAMAM-PEG-cRGD exerted potent siRNA cellular internalization in which transfection efficiency measured by flow cytometry was up to 68% when the charge ratio (N/P ratio) was 3.5. Ligand-receptor affinity together with electrostatic interaction should be involved in the nano-siRNA endocytosis mechanism and we then proved that attachment of cRGD enhanced cellular uptake via RGD-integrin recognition. Gene silencing was evaluated by reverse transcription polymerase chain reaction and PAMAM-PEG-cRGD-siRNA complex downregulated the expression of hERG to 26.3% of the control value. Furthermore, gene knockdown of hERG elicited growth suppression as well as activated apoptosis by means of abolishing vascular endothelial growth factor secretion and triggering caspase-3 cascade in anaplastic thyroid carcinoma cells. Our study demonstrates that this novel triblock polymer, PAMAM-PEG-cRGD, exhibits negligible cytotoxicity, effective transfection, “smart” cancer targeting, and therefore is a promising siRNA nanocarrier. Keywords: small interfering RNA, dendrimer, gene silencing, human ether-à-go-go-related gene, anaplastic thyroid cancer